Queer studies: A lesbian, gay, bisexual & transgender anthology - Beemyn, Genny; Eliason, Michele J. (New York University Press, 1996)
This book is a wide-ranging anthology which discusses the nature and diversity of queer studies, its foundations, and some of the most pressing issues in the field.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; identité sexuelle; identités; identités LGBTQIA2+; philosophie politique; postmodernisme; premier cycle; queer; sciences humaines; sex3383; sexualité; sociologie; thématiques

An intimate distance: women, artists and the body - Betterton, Rosemary.. (Routledge, 1996)
How have women artists taken possession of the female body? What is the relationship between looking and embodiment in art made by women? In a series of original readings of the work of artists from Kathe Kollwitz and Georgia O'Keeffe to Helen Chadwick and Laura Godfrey-Isaacs, Rosemary Betterton explores how women artists have addressed the changing relationship between women, the body and its representation in art. In detailed critical essays that range from the analysis of maternal imagery in the work of German artists at the turn of the century to the unrepresented body in contemporary abstract painting, Betterton argues that women's art practices offer new ways of engaging with our fascinations with and fears about the female body. Reflecting the shift within feminist art over the last decade, An Intimate Distance sets the reinscription of the body within women's art practice in the context of current debates on the body, including reproductive science, maternal subjectivity and the concept of 'body horror' in relation to food, ageing and sex. Drawing on recent theories of embodiment developed within feminist philosophy and psychoanalytic theory, the essays reveal how the permeable boundaries between nature and culture, the female body and technology are being crossed in the work of women artists.
Keywords: 1900-1999; approches et analyses; art contemporain; artistes féministes; arts; corps; cours; discipline; europe; femmes* artistes; féminisme pop; har4600; histoire de l'art; premier cycle; périodes historiques; royaume-uni; régions géographiques; thématiques

Garçons et filles : stéréotypes et réussite scolaire - Bouchard, Pierrette; St-Amant, Jean-Claude (Itinéraires féministes, 1996)
En vue de comprendre les mécanismes menant à la réussite scolaire au secondaire, la recherche se penche sur les modèles d'identification qu'offrent, aux garçons et aux filles, les stéréotypes sexuels. Elle vérifie, à l'aide d'une enquête auprès de 24 écoles secondaires québécoises, le degré d'adhésion aux stéréotypes et son influence sur les rapports entretenus avec l'école. Elle démontre qu'un meilleur rendement scolaire passe par un affranchissement des modèles de sexe. Questionnaire en annexe.
Keywords: approches et analyses; cours; discipline; premier cycle; psy4910; psychologie; recherche quantitative; sciences humaines; sexisme; stéréotypes de genre; systèmes d'oppressions; systèmes éducatifs; études de genres

Quelle lesbienne êtes-vous? - Causse, Michèle (Parole de lesbiennes, 1996)
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; europe; france; hétéronormativité; identités LGBTQIA2+; inégalités; lesbianisme; paris; premier cycle; périodes historiques; queer; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques

Femmes rebelles : naissance d'un nouveau roman africain au féminin - Cazenave, Odile (L'Harmattan, 1996)
"Femmes rebelles " porte sur la nouvelle génération d'écrivainsfemmes africaines francophones des dix dernières années et l'évolution frappante de leur écriture dans ce court laps de temps. Aux premières oeuvres de témoignage du début des années 80 s'est substituée une deuxième phase montrant une écriture plus agressive, plus revendicatrice : . Ce livre examine le mécanisme de rébellion que les écrivains femmes ont instituées à cet effet dans leur critique de l'Afrique d'aujourd'hui.
Keywords: 1900-1999; 1980-1989; afrique; afro-féminisme; approches et analyses; cours; discipline; fem1000; femmes* noires; féminisme africain; premier cycle; périodes historiques; régions géographiques; thématiques; écriture des femmes*; études littéraires

Mémoires lesbiennes : le lesbianisme à Montréal entre 1950 et 1972 - Chamberland, Line (De mémoire de femmes, 1996)
Line Chamberland retrace la vie de femmes qui ont eu le courage de leurs amours à une époque où la condamnation sociale du lesbianisme était unanime. À partir de nombreux témoignages, l’auteure démontre de quelle façon s’exerçait le contrôle social du lesbianisme, quel rôle jouait la famille et comment diverses instances comme les institutions religieuses, l’appareil judiciaire et les autorités psychomédicales veillaient à ce que ces femmes se conforment aux diktats, les poussant parfois à la marginalité ou les obligeant à adopter diverses stratégies de dissimulation.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; droits des femmes*; histoire et politique; hétéronormativité; hétérosexisme; identités LGBTQIA2+; lesbianisme; montréal; pol4212; premier cycle; périodes historiques; queer; québec; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques; violences

Science, conscience et action : vingt-cinq ans de recherche féministe au Québec - Dagenais, Huguette (Les éditions du remue-ménage, 1996)
Après un quart de siècle de néoféminisme, on connaît encore mal la recherche féministe et l’ampleur du travail accompli par ces chercheuses. Les auteures examinent ici les travaux qui ont porté sur la famille, la conciliation travail-famille et sur l’emploi, ceux qui ont documenté des aspects particuliers de la santé des femmes et de la violence conjugale ainsi que les nombreuses études produites dans le domaine de l’éducation. Elles mettent également en lumière les changements et les résistances révélés par les recherches dans le champ religieux, le champ politique, celui du droit de même que dans le domaine des communications. Ce faisant, elles rendent manifestes les caractéristiques de la recherche féministe québécoise, notamment les liens établis par les chercheuses entre théorie et pratique, recherche et action. Des textes de Pierrette Bouchard, Anita Caron, Renée Cloutier, Christine Corbeil, Huguette Dagenais, René B.-Dandurand, Francine Descarries, Louise Guyon, Thérèse Hamel, Geneviève Martin, Karen Messing, Josée Néron, Ann Robinson, Armande Saint-Jean, Diane-Gabrielle Tremblay et Manon Tremblay.
Keywords: 1900-1999; amériques; conciliation famille-travail; cours; discipline; droit; famille; fem1000; histoire et politique; premier cycle; périodes historiques; québec; régions géographiques; santé; science des religions; science politique; science politique et droit; sciences humaines; thématiques; théologie; violences; violences contre les femmes*

Postcolonial subjects: Francophone women writers - Green, Mary (University of Minnesota Press, 1996)
Sujets postcoloniaux » est un projet collectif centré sur les questions de langue, d'identité et de voix alors qu'ils abordent les questions de genre, de race, d'ethnicité, de culture et de nation. Les essais critiques présentés ici portent sur les contributions littéraires de femmes contemporaines écrivant en français dont les liens culturels, les identités ethniques et les racines historiques se situent au-delà de l'Hexagone, au-delà de la carte à six faces de la France.
Keywords: approches et analyses; cours; discipline; europe; fem1000; france; francophonie; féminisme décolonial; littérature; premier cycle; ressource en ligne; régions géographiques; thématiques; écriture des femmes*; études littéraires

La valence différentielle des sexes au fondement de la société? - Héritier, Françoise (Masculin/féminin. La pensée de la différence., 1996)
Keywords: anthropologie; approches et analyses; cours; cycles supérieurs; différence des sexes; discipline; domination masculine; fem1000; fem7000; premier cycle; rapports sociaux de sexe; ressource en ligne; sciences humaines

Masculin/féminin. La pensée de la différence. - Héritier, Françoise (Odile Jacob, 1996)
Le combat pour l’égalité des sexes est le plus radical qui puisse être. Masculin/Féminin nous montre en effet comment la différence des sexes structure la pensée humaine puisqu’elle en commande les deux concepts primordiaux : l’identique et le différent. La manière dont chaque culture construit cette différence met en branle toute sa conception du monde, sa sociologie et sa biologie comme sa cosmologie. Changer le rapport du masculin et du féminin, c’est bouleverser nos ressorts intellectuels les plus profonds, élaborés au fil des millénaires. En démontant les mécanismes de la différence, ce livre offre des solutions pour parvenir à l’égalité.
Keywords: anthropologie; approches et analyses; cours; cycles supérieurs; différence des sexes; discipline; domination masculine; fem1000; fem7000; lit3220; lit3495; premier cycle; rapports sociaux de sexe; ressource en ligne; sciences humaines; soc3113

Queer theory: an introduction - Jagose, Annamarie (New York University Press, 1996)
The essential history of queer theory The reclamation of the term queer over the last several decades marked a shift in the study of sexuality from a focus on supposedly essential categories such as gay and lesbian, to more fluid notions of sexual identity. On the cutting-edge of this significant shift was Annamarie Jagose’s classic text Queer Theory: An Introduction. In this groundbreaking work, Jagose provides a clear and concise explanation of queer theory, tracing it as part of an intriguing history of same-sex love over the last century. Blending insights from prominent theorists such as Judith Butler and David Halperin, Jagose illustrates that queer theory's challenge is to create new ways of thinking, not only about fixed sexual identities such as straight and gay, but about other supposedly immovable notions such as sexuality and gender, and man and woman. First released almost 25 years ago, this groundbreaking work has provided a foundation for the continuing evolution of queer theory in the twenty-first century.
Keywords: approches et analyses; cours; discipline; histoire; premier cycle; queer; sciences humaines; soc2014; thématiques

I am woman: A native perspective on sociology and feminism - Maracle, Lee (Press Gang, an imprint of Raincoast Books, 1996)
Je suis une femme représente ma lutte personnelle contre la féminité, la culture, les croyances spirituelles traditionnelles et la souveraineté politique, écrite à une époque où cette lutte n'était pas terminée. Mon intention initiale était de donner aux femmes autochtones les moyens de prendre à cœur leur propre lutte personnelle pour être féministe autochtone. Les modifications apportées à cette deuxième édition du texte ne modifient pas mon intention initiale. Cela reste ma tentative de présenter la perspective sociologique d'une femme autochtone sur les impacts du colonialisme sur nous, en tant que femmes, et sur moi personnellement.
Keywords: amériques; approches et analyses; canada; cours; discipline; fem1300; féminisme autochtone; pol4105; premier cycle; régions géographiques; sciences humaines; sociologie

Le Rose et le noir : les homosexuels en France depuis 1968 - Martel, Frédéric (Epreuve des faits, 1996)
"Ce livre est une chronique des homosexuels en France, hommes et femmes, depuis 1968. L’homosexualité est un fil rouge qui relie entre eux des phénomènes majeurs : libération sexuelle, féminisme, mutation des modes de vie, lutte contre le sida, pacs… Frédéric Martel évoque les figures emblématiques et les activistes, mais aussi les débats et les combats, tout ce qui a contribué à ce que les « gais » sortent de l’ombre. Plus visibles, mieux acceptés, les homosexuels sont aujourd’hui en quête de reconnaissance." -- Site de l'éditeur
Keywords: 1900-1999; LGBTQIA2+; activisme; approches et analyses; cours; discipline; discours militant; droits des femmes*; europe; france; his4860; histoire du féminisme; histoire et politique; homosexualité; hétérosexisme; identités LGBTQIA2+; justice sociale; lesbianisme; militance; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexualité; sociologie; systèmes d'oppressions; thématiques

Bisexualité: le dernier tabou - Mendès-Leite, Rommel; Deschamps, Catherine; Proth, Bruno-Marcel (Calmann-Lévy, 1996)
A partir de nombreux témoignages, ce livre dresse un portrait des bisexuels dans leur infinie variété, leur histoire, leur quotidien.
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; approches et analyses; corps; cours; discipline; europe; france; hétérosexisme; identités LGBTQIA2+; inégalités; premier cycle; périodes historiques; queer; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques

The art of reflection: women artists'self-portraiture in the twentieth century - Meskimmon, Marsha.. (Columbia University Press, 1996)
Self-portraiture has long been a means for the male artist to assert an identity as masterful creator or tortured soul; women have overwhelmingly been presented as objects, and rarely as subjects of self-portraiture. In recent years, however, women artists have used their work to disrupt this tradition. With 43 illustrations of works by Louise Bourgeois, Frida Kahlo, Alice Neel, Cindy Sherman, and Jo Spence, among others, The Art of Reflection is the first sustained inquiry into the appropriation of self-portraiture by women. In suggestive critical meditations on paintings, photographic work, sculpture, performance art, and body art, Marsha Meskimmon shows how twentieth-century women artists have undermined male-centered definitions of how "the artist" depicts the self. Drawing upon feminist theory and philosophy from Simone de Beauvoir to Luce Irigaray, The Art of Reflection casts doubt on the idea of self-portrait as a mirror, in which the static self is rendered accurately and naturalistically. Meskimmon evokes a series of myths about what an artist is, how "he" should be represented, and how "his" work is to be read as autobiography. Through close readings of the imaginative self-representations of women artists -as male artist and god, as central player in the studio and in the Christian passion- she shatters these myths. In an absorbing assessment of the ways women artists have negotiated the complex group of roles ascribed to "woman," Meskimmon considers the partially nude painting by pregnant artist Paula Modersohn-Becker and performance artist Annie Sprinkle's confrontation of the thin line between celebration of female sexuality and objectification of the female body. As a nuanced appreciation of the interpretations of self-portraiture among women artists, The Art of Reflection will prove an invaluable resource on a subject that has received little attention from art criticism. Meskimmon's work also presents a bold challenge to critical tradition, compelling readers to rethink the meaning of the genre as a whole.
Keywords: 1900-1999; arts; corps; cours; critique d'art; discipline; femmes* artistes; har4600; histoire de l'art; premier cycle; périodes historiques; représentation; thématiques

La construction du "French Feminism" dans le discours universitaire américain - Moses, Claire (Nouvelles Questions Féministes, 1996)
Les chercheuses en études féministes aux Etats-Unis ont publié de nombreux articles sur le féminisme français; pourtant, peu de féministes françaises s'y reconnaissent ou y reconnaissent leur mouvement. Cet article porte sur la disjonction qui existe entre la version américaine du féminisme français et le mouvement dont la pratique et la théorie ont eu un impact sur la politique, la culture, et la société françaises des vingt dernières années. Cet article part du principe que la version américaine n'est pas simplement une interprétation erronée des faits. Bien que je décrive très brièvement le modèle que les militantes et les critiques féministes ont élaboré, ma contribution porte plus sur l'organisation de la connaissance aux Etats-Unis et l'impact de la recherche féministe américaine sur le mouvement français. Dans le modèle américain du féminisme français, les théoriciennes Hélène Cixous, Julia Kristeva, et Luce Irigaray, ainsi que le groupe Psychanalyse et Politique sont pris comme modèles. Le militantisme s'efface devant la théorie, les théories matérialistes devant le post-structuralisme, la dimension sociale et historique devant le discours littéraire et philosophique. Pourquoi en est-il ainsi? Quels a priori politiques se cachent derrière la version américaine du féminisme français? Cet article a pour objectif d'avancer quelques réponses et de soulever plus encore de questions. Ce faisant, j'espère mettre à jour la diversité des engagements politiques conflictuels qui façonnent la recherche intellectuelle aux Etats-Unis et montrer les conséquences variées et pas toujours voulues de celle-ci. Much has been written in U.S. feminist scholarship about "French feminism", but few French feminists recognize themselves or their movement in these studies. This article looks at this disjunctive between the American version of "French feminism" and the movement whose practice and theory had an impact on French politics, culture, and society over the past two decades. The premise of the article is that the disjunctive is not simply a matter of "getting the story wrong". Although I describe (very briefly) the movement that feminist activists and scholars have constructed for themselves, the interest of this paper is more so on the construction of knowledge in the U.S. and the impact of U.S. feminist scholarship on the French movement. In the American construction of "French feminism", theorists Hélène Cixous, Julia Kristeva, and Luce Irigaray, along with the group Psychanalyse et politique, are the significant exemplars. Theory is privileged over activism, poststructuralism over materialist theories, literary and philosophical discourse over the social and historical. Why? What political assumptions are embedded in the U.S. construction of "French feminism'"? This paper intends to offer some answers (and raise many more). In so doing, I hope to make clear the variety of conflicting political agendas that inform U.S. intellectual work and the variety of consequences, not always intended, that this work has had.
Keywords: 1900-1999; amériques; cours; débat; europe; fem1000; france; histoire et politique; militance; premier cycle; périodes historiques; ressource en ligne; régions géographiques; thématiques; états-unis

Generations & geographies in the visual arts: feminist readings - Pollock, Griselda.. (Routledge, 1996)
In Generations and Geographies, the challenge of contemporary feminist theory encounters the provocation of the visual arts made by women in the twentieth century. The major issue is difference: sexual, cultural and social. Generations points to the singularity of each artist's creative negotiation of time and historical and political circumstance; Geographies calls attention to the significance of place, location and cultural diversity, connecting issues of sexuality to those of nationality, imperialism, migration, diaspora and genocide.Generations and Geographies is framed by theoretical debates in cultural analysis by Griselda Pollock, Mieke Bal, Elisabeth Bronfen and Irit Rogoff, and two historical analyses of representations of the female nude by Rosemary Betterton and Nanette Salomon. Essays on international contemporary art discuss artistic practice by women working in both western and non-western contexts, focusing on themes of the mother, the body, the land and history/memory. The artists discussed include the French performance artist Orlan, the Cuban American artist Ana Mendieta and Jenny Saville from Britain, the Chilean artist Cecilia Vicuna, Shimada Yoshiko from Japan, the Korean artist Re-Hyun Park and the Korean/Canadian artist Jin-me Yoon, Bracha Lichtenberg Ettinger from Israel and the American artist Cindy Sherman. British/Zanzibari artist Lubaina Himid provides specially commissioned artists' pages on the theme of history, location and displacement.
Keywords: 1900-1999; approches et analyses; arts; arts visuels et médiatiques; corps; cours; discipline; har4600; histoire de l'art; histoire et politique; intersectionnalité; maternité; point de vue situé; premier cycle; périodes historiques; ressource en ligne; thématiques

Queer theory/sociology - Seidman, Steven (Twentieth-century social theory, 1996)
Bringing together some of the classic sociological statements and the new sociology of homosexual desire, this book points to new synthetic approaches to queer studies. It aims to productively engage the pioneering work of queer theorists.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; approches et analyses; cours; discipline; premier cycle; périodes historiques; queer; sciences humaines; soc2014; sociologie; sofia; thématiques

Feminist theorists: Three centuries of women's intellectual traditions - Spender, Dale (Women's Press, 1996)
Feminism was not born in 1968. Yet the work of three centuries of feminist thinkers has been dismissed, distorted or forgotten. Even the names of many of them remain unfamiliar, and few have so much as a mention in history books. Feminist Theorists demonstrates once and for all that we can no longer be content with received ideas about 'progress', which may explain the world for men, but which fail to make sense of the historical experience of women. It shows too that contemporary women have a rich intellectual tradition on which to draw for stimulus, inspiration and enjoyment.
Keywords: approches et analyses; cours; discipline; fem1000; histoire; histoire et politique; justice sociale; mouvements féministes; premier cycle; sciences humaines; thématiques; théories féministes

The rejected body: feminist philosophical reflections on disability - Wendell, Susan (Routledge, 1996)
''Susan Wendell has lived with Chronic Fatigue Syndrome (Myalgic Encephalomyelitis) since 1985. In The Rejected Body, she connects her own experience of illness to feminist theory and the literature of disability. The Rejected Body argues that feminist theorizing has been skewed toward non-disabled experience, and that the knowledge of people with disabilities must be integrated into feminist ethics, discussions of bodily life, and the criticism of the cognitive and social authority of medicine.''
Keywords: 1900-1999; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; capacitisme; corps; cours; discipline; inégalités; phi4336; philosophie; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; états-unis

Inside the visible: an elliptical traverse of 20th century art in, of, and from the feminine - Zegher, M. Catherine de; Institute of Contemporary Art (Boston, Mass); Kanaal Art Foundation.; Zegher, M. Catherine de; Institute of Contemporary Art (Boston, Massachusetts); Kanaal Art Foundation. (MIT Press, 1996)
Published on the occasion of a major exhibition opening at the Institute of Contemporary Art in Boston, Inside the Visible presents a gendered reading of more than thirty women artists of vastly different background and experience. The work of important yet previously "invisible" figures is highlighted alongside the work of established artists to create a retheorized interpretation of the art of this century. Structured in terms of recurrent cycles over time, Inside the Visible focuses on three periods (the 1930s and 1940s, the 1960s and 1970s, and the 1990s) that anticipated a wave of political repression, nationalism, and xenophopia, often stimulating artistic production that redefined practice. Illustrated essays document each artist in the collection. In addition, four general essays trace the connections among the artists. These take up such issues as why artistic recognition eluded certain artists and why their work is only just becoming visible today. They also address overlapping themes such as gender and sexuality; the intersection of racial, class, ethnic, sexual, and regional identities; and the nature of the relationship between work and viewer.
Keywords: 1900-1999; 1930-1939; 1940-1949; 1960-1969; 1970-1979; 1990-1999; approches et analyses; artistes féministes; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; intersectionnalité; premier cycle; périodes historiques; queer; thématiques